PERILAKU MASYARAKAT TERHADAP PENGGUNAAN DAN PELESTARIAN AIR DI LINGKUNGANNYA (STUDI KASUS DI DAERAH ALIRAN SUNGAI GARANG, SEMARANG) (Faculty of Social Science, Universitas Negeri Semarang, 2008)
One of external factors which contribute to the occurrence of floods and flash floods at Garangwatersheds is socio hidraulic character (water culture). The inhabitants water culture of the Garangwatersheds belongs to the low category. It is reflected from several behaviors: they channels velocity thesurface runoff to the river, lack to act on environment and small river conservation, garbage disposal tothe river and they are not making every effort infiltrated the surface runoff.Keywords : Water culture, watersheds, infiltration, surface runoff, flash flood